Recursos lingüísticos e paralingüísticos na clínica fonoaudiológica do autismo - Lima, Andréa Novaes Ferraz de (2007)
Nowadays, the brazilian speech therapy clinic, with autistics, is still dominated by the use of corrective and normative procedures, aiming at communication basically. Moving away from the positivism s point of view and adopting the subjectivism ideas (that values the particular), beyond the language conception as a mean of action and the dialogic game as a joint construction of meanings, this research investigated the role of the verbal-linguistic resources, prosodics and paralinguistics in the construction of the autistic child language, in the speech therapy clinic. Specifically, this study had the objective of searching the conversation marks basically the interactionals and the catenation ones, the vowels prolongations, intonations, rhythm and vocal pitches alterations, the cinesic, the tacesic, the prosemic, the correction, the paraphrasing, the repetition, the pause, the hesitation, the interruption and the silence. It was also verified the incidence of these resources en the relation between the autistic child and the speech therapist. The participants of the study were two speech therapists and their patients, among eight and twelve years old, with autism diagnostic, characterized, in this research, as 1 and 2 diade. The data collection was done weekly, through video recorders, gotten during the speech therapy sections. The data were analyzed by means of the video recorders transcriptions, with basis in the discursive fragments, in agreement to the purposes of the Conversation Analysis. The results demonstrated the role played by the resources in the dialogic interactions in the therapists speech turns and in their patients turns. It was observed an equilibrium in the use of the resources by the speech therapists and an inaquality with prevalence of paralinguistic resources by the patients. This study noticed the use of babbling or echolalia by the patients, considering the relation with the repetitions (essencial resource to the speech). With the intention of establish a contrast between the resources, it was required a detailed overlook from the video recorders, and, later, an analisys about the echolalia behavior all along the interactions analysed. As a conclusion, the verbal-linguistic resources, prosodics and paralinguistics were current during the díades interactions. The balanced use of the resources envolved, as the observed in the therapists speech turn, allowed a better speech constructuion. It was also evidenced the imediatism existent in the face-to-face interaction, and that it is very hard to certify the difference between the echolalia or babbling and the repetition. Therefore, this difficulty suggests that both must be meaned in the therapy process, allowing big discursive possibilities to the speakers.